2022
DOI: 10.3389/fmicb.2022.1000419
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms have a minor impact on autism spectrum disorder and associations with gut microbiota and short-chain fatty acids

Abstract: Children with autism spectrum disorder (ASD) experience gastrointestinal (GI) issues more frequently and severely than children who are typically developing (TD). The connections between gastrointestinal problems, microbiota, and short-chain fatty acids (SCFAs) in ASD are still being debated. We enrolled 90 children, 45 of whom were diagnosed with ASD, and examined the impact of GI disorders on ASD. The six-item GI Severity Index questionnaire was used to evaluate gastrointestinal symptoms, while the Social Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…However, the role of SCFAs in ASD pathology remains controversial. Some clinical studies also reported no difference or even higher concentrations of SCFAs in ASD children ( 32 , 33 ). These altered fecal SCFAs can be related to many factors, such as increased probiotic use, gut dysbiosis, impaired gut permeability, and so on ( 34 ).…”
Section: Discussionmentioning
confidence: 97%
“…However, the role of SCFAs in ASD pathology remains controversial. Some clinical studies also reported no difference or even higher concentrations of SCFAs in ASD children ( 32 , 33 ). These altered fecal SCFAs can be related to many factors, such as increased probiotic use, gut dysbiosis, impaired gut permeability, and so on ( 34 ).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, it can lead to gliosis, a neuro-inflammatory response [118]. Curiously, high levels of Bacteroidetes and elevated PPA levels were reported in children suffering from ASD [121,122]. Additionally, PPA administration used to generate a rodent model of ASD resulted in brain morphological changes, including alterations in the size and structure of the cortex, hippocampus, and amygdala, brain regions that are associated with the regulation of social behavior and cognition [123].…”
Section: Scfas-asdmentioning
confidence: 99%
“…Moreover, it can lead to gliosis, a neuro-inflammatory response [104]. Curiously, high levels of Bacteroidetes and elevated PPA levels were reported in children suffering from ASD [107,108]. Additionally, PPA administration used to generate a rodent model of ASD, resulted in brain morphological changes, including alterations in the size and structure of cortex, hippocampus and amygdala, brain regions that are associated with regulation of social behavior and cognition [109].…”
Section: Scfas-asdmentioning
confidence: 99%